Grain boundary diffusion of titanium in polycrystalline quartz and its implications for titanium in quartz (TitaniQ) geothermobarometry. (1st April 2016) - Bromiley, Geoffrey David; Hiscock, Matthew
Abstract: We have performed a series of experiments to measure diffusivity of Ti in polycrystalline quartz under high pressure/temperature, nominally anhydrous conditions. Resulting diffusion profiles reveal operation of both slow lattice diffusion and faster grain boundary diffusion. Over the temperature range investigated, 1000–1400 °C, grain boundary diffusion of Ti is between 3 and 4 orders of magnitude faster than lattice diffusion and can be expressed by the following Arrhenius relationship: D ( m 2 / s ) = 2.00 ± 0.08 × 10 7 exp ( - 195 ± 7 kJ . mol - 1 / RT ) . Grain boundary diffusion is expected to have a considerable influence on Ti mobility in the crust in Si-rich rocks under fluid-absent conditions, especially in fine-grained rocks, with grain boundaries acting as fast conduits for transporting Ti. This has important consequences for the application of Ti in quartz geothermobarometry (TitaniQ). Grain boundary diffusion is a viable mechanism for re-equilibrating Ti contents in quartz-rich rocks to lower values, for example during dynamic recrystallization. This implies that TitaniQ can be applied to relatively low temperatures (below 600 °C) although zonation of Ti contents in larger quartz grains is expected due to the relative sluggishness of lattice diffusion under these conditions and because fast diffusion in grain boundary regions effectively inhibits growth entrapment. Grain boundary diffusion for Ti also has implications for the activity of Ti in quartz-rich rocks and application of the TitaniQ geothermobarometer.